THE USE OF THE BODY COMPOSITION ANALYZER IN ASSESSING THE HEALTH OF YOUTH STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
The main focus of the study was on determining body composition, in particular the amount of adipose tissue, and metabolic age of 18-19 year old higher education students of Khmelnytskyi National University, who study in the specialty 017 "Physical Culture and Sports" and in the subject specialty 014.11 Secondary Education (Physical Culture). To obtain empirical data, the bioimpedance method was used, in particular the Tanita RD-545 body composition analyzer.In addition to determining the average group data on the content of adipose tissue, visceral fat, metabolic age, basal metabolic rate, the relationships between these indicators were calculated. Regarding the content of adipose tissue, differences were established between boys and girls. In boys, the content of adipose tissue is 13.92%, in girls 23.25%. In general, the average data indicate that according to these indicators, the composition of the body corresponds to the norm. The metabolic age of the subjects is 2.9 years (in boys) and 3.1 years (in girls) ahead of the chronological age. A positive result was established regarding the content of visceral fat in the body of students 2.36% in boys and 1.08% with a norm of up to 12%. In the vast majority of 74.3% of higher education applicants, the amount of visceral fat is at a minimum level and is equal to 1%.Correlation analysis allows us to state that the best indicators of metabolic age are those higher education students who have a lower body weight and have less absolute and relative body fat. This gives grounds to state that to maintain health it is extremely important to monitor body weight and the content of adipose tissue in the body.
Keywords: adipose tissue; body composition; metabolic age; bioimpedance method